Corticosterone Inhibits LPS-Induced NLRP3 Inflammasome Priming in Macrophages by Suppressing Xanthine Oxidase. (18th May 2020) - Wu, Ling; Zhou, Chengfu; Wu, Jianfeng; Chen, Shikun; Tian, Zedan; Du, Quan
Abstract : Following traumatic insult and associated pathogen infection, innate immunity is activated during the perioperative period, especially the NLRP3 inflammasome in macrophages. The neuroendocrine response is also rapidly activated to regulate excessive inflammation; however, the molecular mechanisms are still not completely clear. This study is aimed at investigating the modulation of NLRP3 inflammasome priming by endogenous glucocorticoids (corticosterone, CORT) and its relationship with xanthine oxidase (XO). RAW264.7 murine macrophages were stimulated with LPS (1  μ g/ml). LPS-induced NLRP3 expression was pretreated by CORT at different concentrations (0-900 ng/ml). Then, the effect of higher concentrations of CORT (700 ng/ml) on LPS-induced NLRP3 expression and the effect of allopurinol (250  μ g/ml) were observed. Finally, the effects of a CORT antagonist (RU486) on XO expression and activity and NLRP3 expression in macrophages were further analyzed. Supernatant levels IL-1 β and IL-18 were measured. The results showed that LPS-induced NLRP3 expression was upregulated further by pretreatment with CORT (300 ng/ml) (P < 0.05 ); however, higher concentrations of CORT (greater than 700 ng/ml) downregulated NLRP3 expression (P < 0.01 ) and the expression and activity of XO (P < 0.05 and P < 0.01, respectively). Allopurinol significantly inhibited NLRP3 expression. However, XO expression and activity, NLRP3 expression, and supernatant IL-1 β and IL-18 levels were significantly increased in the RU486 group compared with the CORT group. In conclusion, our results suggested that CORT inhibits LPS-induced NLRP3 inflammasome priming in macrophages. The underlying mechanism is related to the modulation of XO expression and activity, which may be involved in priming and activating the NLRP3 inflammasome.